Relationship between Biological and Qualitative Indices in Surface Waters Receiving the Effluent of Fish Farms in the Northwest of Iran - Farhad Pourfaraj; Malek Abazari; Eslam Moradiasl; S. Amad Mokhtariai (Journal of Arthropod-Borne Diseases)
Background: Water quality is usually measured using various indicators based on physical, chemical and biological parameters. By using the biological index that is based on the identification of the arthropod families, it is possible to make a logical judgment about the ecosystem condition. The aim of this study was measuring correlation coefficients between qualitative and biological Indices.